2000
DOI: 10.21273/jashs.125.4.413
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate Reserve Concentrations and Flower Bud Density Effects on Vegetative and Reproductive Development in Southern Highbush Blueberry

Abstract: Vegetative budbreak, leaf area development, and fruit size in southern highbush blueberry (Vaccinium corymbosum L. interspecific hybrids) decrease as flower bud density increases. The effect on fruit size has been attributed to both insufficient carbohydrate reserves and reductions in current photoassimilates caused by decreased vegetative growth. Experiments were conducted with two southern highbush blueberry cultivars, `Misty' and `Sharpblue', to test the hypothesis that in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Our analyses indicated that fruit ripening efficiency (as measured by ripe fruit production per node), reproductive node maintenance rate (as measured by proportion node success), and fruit dry mass content may be three traits that must decline relatively more steeply as reproductive effort increases. These results are consistent with current thoughts on resource prioritization and limitation (Brown & McNeil, ; Maust et al., ). If a plant can produce many fruit, selection may favor prioritizing the highest‐quality of these instead of equal investment across all of them (Brown & McNeil, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our analyses indicated that fruit ripening efficiency (as measured by ripe fruit production per node), reproductive node maintenance rate (as measured by proportion node success), and fruit dry mass content may be three traits that must decline relatively more steeply as reproductive effort increases. These results are consistent with current thoughts on resource prioritization and limitation (Brown & McNeil, ; Maust et al., ). If a plant can produce many fruit, selection may favor prioritizing the highest‐quality of these instead of equal investment across all of them (Brown & McNeil, ).…”
Section: Discussionsupporting
confidence: 91%
“…The sixth trait, ripe fruit production per node, did not increase in response to standard flower removal in this study but did increase in response to biased flower removal (Table ). Increases in vegetative mass (Hartemink et al., ; Maust et al., ), leaf area (Karlsson, Andersson, & Svensson, ; Maust et al., , ), fruit ripening rate (Maust et al., , ; Valantin‐Morison, Vaissière, Gary, & Robin, ), and fruit dry mass (Vallius, ) have all been reported in previous flower removal studies. However, we have found no studies besides ours that have reported significant removal effects on proportion node success or fruit titratable acidity.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In our study, the shoots remaining inside the dark or low light grow tube would likely have been a sink, depleting reserves in the crown and roots. Later in the season, blueberry plants export carbohydrates, from photosynthesis, to the crown and roots and carbohydrate and nitrogen reserves in the roots, crown, and older canes are important for early-season growth (Bañados et al, 2012;Maust et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In the period leading up to dormancy, fruit trees will accumulate total NSCs, which are then translocated into storage areas including buds, trunk, and roots (Gaudillère et al, 1992;Loescher et al, 1990). NSCs play an essential role in initiating and maintaining growth (Flore and Layne, 1999;Keller and Loescher, 1989;Maust et al, 2000;Rady and Seif El-Yazal, 2013) during periods of stress (such as dormancy, the breaking of dormancy, and initial stages of bud burst). In many fruit trees, including sweet cherry, flower buds develop earlier than vegetative buds; therefore, bud NSC reserves are critically important in initiating bud burst and must be sufficient or remobilized from other storage organs (Ben Mohamed et al, 2012;Cerasoli et al, 2004;Marafon et al, 2011;Richardson et al, 2010;Vasudevan et al, 1998) until photosynthetic leaf area can provide adequate photosassimilate to developing sinks (Dejong and Grossman, 1995;Flore and Layne, 1999).…”
mentioning
confidence: 99%